Abdominal massage alleviates functional diarrhea in immature rats via modulation of intestinal microbiota and tight junction protein - Huang, Yanyi; Ma, Qing; He, Jingxin; Liang, Xingshan; Mai, Qingxin; Luo, Huifang; Hu, Jingyi; Song, Yang (Frontiers in Pediatrics, 2022)
Functional diarrhea (FD) is a common type of chronic diarrhea in children. Recurrent diarrhea can negatively impact children's quality of life and raise healthcare costs significantly. However, conventional treatments are ineffective and limited. Moreover, children with chronic conditions have poor medication compliance. Therefore, nonpharmacological and complementary treatments are urgently needed. In China, abdominal massage is widely used to treat diarrhea in children. Numerous clinical studies have verified its usefulness in treating gastrointestinal disorders as well. Nevertheless, its intrinsic mechanisms are still unclear, and the impact of massage direction on treatment effects has received less attention. In our study, we found that FD was not associated with pathogen infection. A dysbiosis of the intestinal microbiota and disruption of the intestinal barrier are most likely to cause FD. Moreover, this study also substantiates that abdominal massage can mitigate functional diarrhea by altering the intestinal microbiota structure and decreasing the number of bacteria that damage intestinal mucosal barriers. The reduction of Ruminococcus_torques_group and Clostridium_innocuum_group at the genus level potentially mediated the beneficial effects of abdominal massage on alleviating diarrhea. Furthermore, massaging from two different directions, clockwise (CW) and counter-clockwise (CCW) massage, would not significantly influence the effect of the massage on intestinal microbiota or tight junction proteins. In summary, abdominal massage is an effective complementary therapy for children suffering from functional diarrhea.